2004
DOI: 10.1074/jbc.m405135200
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Respiratory Chain Is Partially Organized in a Supercomplex Assembly

Abstract: The model of the respiratory chain in which the enzyme complexes are independently embedded in the lipid bilayer of the inner mitochondrial membrane and connected by randomly diffusing coenzyme Q and cytochrome c is mostly favored. However, multicomplex units can be isolated from mammalian mitochondria, suggesting a model based on direct electron channeling between complexes. Kinetic testing using metabolic flux control analysis can discriminate between the two models: the former model implies that each enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(191 citation statements)
references
References 52 publications
14
169
1
4
Order By: Relevance
“…We therefore attempted to determine which mechanisms regulate OXPHOS gene expression in human muscle. A nuclear-encoded gene, NDUFB6 (from complex 1 in the respiratory chain), was selected for this analysis because its expression is significantly reduced in diabetic muscle, the NDUFB6 gene is located under a linkage peak for T2DM on chromosome 9, and complex 1 is suggested to be rate limiting for NADH oxidation (3,9,11,12). The key finding of the present study was that genetic (polymorphism), epigenetic (DNA methylation), and nongenetic (e.g., age) factors were associated with the expression level of NDUFB6 in human skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore attempted to determine which mechanisms regulate OXPHOS gene expression in human muscle. A nuclear-encoded gene, NDUFB6 (from complex 1 in the respiratory chain), was selected for this analysis because its expression is significantly reduced in diabetic muscle, the NDUFB6 gene is located under a linkage peak for T2DM on chromosome 9, and complex 1 is suggested to be rate limiting for NADH oxidation (3,9,11,12). The key finding of the present study was that genetic (polymorphism), epigenetic (DNA methylation), and nongenetic (e.g., age) factors were associated with the expression level of NDUFB6 in human skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the effect of age on mitochondrial function can be determined by both genetic and epigenetic factors. To address this we selected the NDUFB6 gene from the first respiratory complex for further studies, because NDUFB6 is among the set of OXPHOS genes showing significant reduction in muscle from patients with T2DM compared with healthy control subjects and because the first complex has a key role in regulating OXPHOS (3,9). We specifically examined whether polymorphisms in the promoter of the gene were associated with an age-dependent impact on gene expression and/or risk of T2DM and whether this was modified by epigenetic factors like DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the Q pool is partitioned such that the ubiquinol produced by complex I is channeled to complex III within supercomplex assemblies, whereas the ubiquinol produced by complex II diffuses into the membrane to access a separate complex III population (13,15). If this is the case, then adding either NADH or succinate to mitochondrial membranes or SMPs should reduce only part of the complex III population, whereas adding both simultaneously should reduce the whole population.…”
Section: Confirmation Of the Presence Of Supercomplexes In Submitochomentioning
confidence: 99%
“…The most widely cited evidence for a catalytic role, from flux control analysis (15), was considered to support substrate channeling between enzymes present within respirasomes. More recently, the existence of dedicated Q and cyt c pools within supercomplex assemblies was proposed to determine electron transport chain flux, based on the relative rates of complex I-and complex II-linked respiration observed when complexes I and/or III are ablated (13).…”
mentioning
confidence: 99%
“…This is highly relevant because RC complexes associate in higher order assemblies called supercomplexes or respirasomes (Schagger and Pfeiffer, 2000;Schagger and Pfeiffer 2001;Schagger, 2002;Bianchi et al, 2004;Schagger et al, 2004;Dudkina et al, 2005, Boekema andBraun, 2007;Acin-Perez et al, 2008;Dudkina et al, 2011), which have been suggested to offer structural and functional advantages to the system, such as the prevention of the destabilization and degradation of RC complexes, the enhancement of electron transport efficiency and substrate channeling, or the reduction of electron or proton leakages Koopman et al, 2010;Lenaz and Genova, 2010). As a consequence of their organization in the respirasomes, structural interdependences amongst the individual RC complexes exist (Acin-Perez et al, 2004;Schagger et al, 2004;D'Aurelio et al, 2006;Diaz et al, 2006;Li et al, 2007;Saddar et al, 2008;Soto et al, 2009;Vempati et al, 2009).…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 99%